PEMASARAN RELASIONAL BERBASIS KOMUNITAS SEBAGAI STRATEGI MENINGKATKAN DAYA SAING SEKOLAH DI DAERAH PINGGIRAN - Muhammad Aryo Ramadhan; Rini Setyaningsih; Eli Sabrifha (Jurnal Manajemen Pendidikan, 2026)
Competition among educational institutions is becoming increasingly complex, particularly for schools located in rural or peripheral areas that face limited facilities, a shortage of feeder schools, and restricted access to information. These conditions demand school management strategies that can enhance competitiveness through approaches that not only rely on academic performance but also strengthen social relationships with the surrounding community. This conceptual study aims to analyze the concept of relationship marketing within the educational context, examine the relevance of community-based approaches in improving school competitiveness, and formulate a conceptual model of community-based relationship marketing suited to the characteristics of schools in peripheral regions. The research employs a literature review method with a descriptive qualitative analysis, involving the examination of books and journal articles related to community engagement and school marketing. The findings indicate that community-based relationship marketing, through trust building, strengthening social bonds, establishing two-way communication, and integrating school programs with local contexts, can serve as an effective strategy to enhance school reputation, community participation, and overall attractiveness. The proposed conceptual model is expected to provide an alternative strategy that can be sustainably implemented by schools in peripheral areas to improve their competitiveness amid the increasingly dynamic landscape of educational competition.